大班教學環境中即時反饋及適性化學習系統的應用對大學生學習成效和投入的影響 - 邱華慧(Hua-Huei Chiou) (Shizi Peiyu Yu Jiaoshi Zhuanye Fazhan Qikan, 2020)
The purpose of this study is to investigate the application of an Interactive Response System （IRS）and an adaptive learning system in a professional course for college students and the effects of their learning outcome and course engagement. The study is conducted for the course “Child Observation" in the Department of Child Care. A quasi-experimental design is adopted with 130 research subjects from three classes, and the course contents of these three classes are the same. One experimental class of 48 students uses IRS in the teaching of the course, another experimental class of 48 students uses IRS and an adaptive learning system, and the traditional lecture and discussion method is used in the control class of 34 students. Research results show that IRS might benefit students’ performance in mid-term and final examinations, but the adaptive learning system does not significantly influence students’ learning performance. The results also show problem solving strategies that are beneficial for improving stu